Daños por Sennius amazonicus, Sennius sp. y Amblycerus sp. (Coleoptera: Bruchidae) en semillas de Sclerolobium sp. (Leguminosae) . - Porto Santos, Germi (Universidad de Costa Rica, 1997)
Seeds of Sclerolobium sp.(N=l000), collected in two localities of Vicosa, Minas Gerais State, Brazil were damaged by bruchid beetles: Sennius amazonicus, and two undescribed species of Sennius and Amblycerus. Total seed darnage was 22.3±1.93% including 3.40±0.97% of darnage by Amblycerus sp. Other agents contributed to seed darnage including O.9±O.4% by fungi. Eighty seven mg of Sclerolobium sp. seeds were necessary Cor development oC either S. amazonicus or Sennius sp. which represented 38.32% of one seed of Sclerolobium sp.